2016
DOI: 10.18203/2394-6040.ijcmph20161386
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on depression, anxiety and their associated factors among medical students in Jhansi, Uttar Pradesh, India

Abstract: Background: Medical College is recognized as a stressful environment that often exerts a negative effect on the academic performance, physical health and psychological wellbeing of the student. Depression and anxiety among medical students is an area of increasing concern worldwide. This study aimed to assess the prevalence of depression, anxiety and its associated factors among medical students in Jhansi, India. Methods: : A cross-sectional study was conducted on medical students from the first to fourth year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 12 publications
5
30
2
5
Order By: Relevance
“…6 The prevalence of anxiety was 54.97% in this study, where as it was 66.9% in a study conducted at Bhubaneswar and it was found to be as high as 71% in a study conducted at Jhansi. 4,5 The prevalence of stress was 45.7% in this study, whereas it was 53% in the study conducted at Bhubaneswar. 4 The study conducted at Basra showed the prevalence of stress to be 44.6% and the study at impala showed 28.4% of the students were under stress.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…6 The prevalence of anxiety was 54.97% in this study, where as it was 66.9% in a study conducted at Bhubaneswar and it was found to be as high as 71% in a study conducted at Jhansi. 4,5 The prevalence of stress was 45.7% in this study, whereas it was 53% in the study conducted at Bhubaneswar. 4 The study conducted at Basra showed the prevalence of stress to be 44.6% and the study at impala showed 28.4% of the students were under stress.…”
Section: Discussioncontrasting
confidence: 61%
“…7,8 A significant association was found between alcohol and depression, alcohol and stress, alcohol and anxiety, smoking and stress and stress with unsatisfaction with studies whereas association was found between substance abuse and anxiety (p≤0.01) and substance abuse with depression (p≤0.01) in a study conducted at Jhansi. 5 The study at Bhubaneswar showed significant association of Smoking, alcohol with depression, anxiety and stress. 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Gender did not have significant association with either anxiety or depression as was seen in a study conducted by Sidana, Kishore, et al 12 It was observed in our study that presence of depression was significantly associated with presence of co-morbidities such as T2DM, HTN, Asthma, etc. ; no.…”
Section: Discussionsupporting
confidence: 49%
“…[14] However, another study by Yadav, Gupta and Malhotra found contrasting results, wherein females had higher prevalence of depression than males. [15] Second year students had the highest prevalence of severe (31%) and extreme (33.3%) depression. It was also observed that those students who had never failed and those who had failed once had the highest prevalence of extreme depression (7.1%).…”
Section: Depressionmentioning
confidence: 95%